The practices of zakat payment by Islamic financial institution in Malaysia - Rosele, Muhammad Ikhlas; Luqman, Abdullah (2018)
The issue of zakat payment by legal entities or companies remains a dispute among current intellectuals. The bigger question arises regarding the capacity of company to become a zakat payer. In Malaysia, zakat payment is not only made by individuals but also made by establishment such as companies. Therefore, this article was developed to conduct a survey regarding the practice of zakat payment by companies, especially the Islamic financial institution in Malaysia. In this study, qualitative approach is used and analysis was carried out on the basic of the payment, types of zakat, and the method of zakat calculation by Islamic financial institution in Malaysia.